SPIRITUAL RELATIONSHIP BETWEEN WELLBEING AND QUALITY OF LIFE IN ELDERLY PEOPLE WITH HYPERTENSION IN PUSPAN VILLAGE, MARON DISTRICT, PROBOLINGGO REGENCY - Ita Jauharatul Kamilah; Nafolion Nur Rahmat; Ro’isah (Media Inovasi Pendidikan dan Publikasi, 2023)
Hypertension is a clinical condition when systolic and diastolic measurements are more than 120 mmHg and 80 mmHg which can be interpreted as an increase in blood pressure from normal limits. The majority found that patients with hypertension have poor quality of life. This study aims to determine the relationship between spiritual well-being with the quality of life in the elderly with hypertension in Puspan Village Maron, Probolinggo This research is a correlational analytic research with a cross sectional research design. This research was conducted in Puspan Village, Maron Probolinggo on 03-07 June 2022 which was conducted door to door. The population of the study was 60 respondents. The sampling technique was carried out using Simple Random Sampling. 51 respondents who match the standards for research inclusion make up the sample.The research instrument used the SWBS spirituality wellbeing scale questionnaire and the WHOQOL-BREF questionnaire. The Spearman rank test was employed in this study's data analysis. The results showed that most of the spiritual wellbeing data were high spiritual well-being, namely 36 respondents (70%). The quality of life is mostly good quality of life, namely 37 respondents (72%). The results of the Spearman rank test showed that the p value = 0.023 so that the p-value < = 0.05. As a result, it can be concluded that there is a correlation between spiritual wellbeing and quality of life in elderly hypertensive patients. It is intended that the elderly will place a greater emphasis on their spiritual health in order to improve their quality of life.